Adapting water management in India to climate change: institutions, networks and barriers. - Azhoni, Adani (Cranfield University, 2017)
Climate change is experienced most through the medium of water. The ability of water institutions and the factors that enable or hinder them to purposefully adapt to the new and additional challenges brought by climate change require better understanding. Factors that influence their perception of climate change impacts and initiatives being taken for adaptation are shaped by various enabling factors and barriers through the interaction with both governmental and non-governmental institutions across administrative scales. Better understanding of these adaptation enablers and barriers is essential for devising adaptation strategies. This research aims to identify and expound the characteristics that enable or hinder institutions to adapt for water management, and hence, it evaluates the involvement of key governmental and non-governmental institutions in India and the inter-institutional networks between them. It surveyed webpages and online documents of sixty Union Government institutions and interviewed representatives from twenty-six governmental, non-governmental, research and academic institutions operating at the national level and another twenty-six institutions operating within the State of Himachal Pradesh in India to assess the characteristics that enable or hinder adaptation. While the online projection of institutional involvement and interaction among key Union Government institutions on climate change and water indicate a more centralized network pointing to Planning Commission and Ministry of Environment and Forest, the interview responses indicated a more distributed network with both Ministries of Water Resources and Environment and Forest recognized as key institutions thereby indicating a potential variation in perception of who is in-charge. Moreover, online documents show institutions that are involved in water have less mention of climate change compared to Union Government ministries involved in less climate-sensitive sectors indicating that impacts of climate change on water are potentially ignored. While it is evident that research and consulting institutions engaging with both national and state level institutions play a key role in enabling adaptation, various barriers pertaining to data and information accessibility, inadequacy of resources and implementation gaps exist particularly due to inter-institutional network fragmentations. Although barriers identified in this study bear resemblance to barriers identified by other researchers in other contexts, this research shows similar barriers can emerge from different underlying causes and are highly interconnected; thereby indicating the need for addressing adaptation barriers collectively as a wider governance issue. Since many of the adaptation barriers emerge from wider governance challenges and are related to larger developmental issues, the findings have important policy implications. Among the various issues that the government needs to address is improving the inter-institutional networks between water institutions so that information dissemination, sharing of learning experiences and data accessibility is improved and prescriptive legislations are seen to be inadequate in this regard. Restructuring the way officials in government water institutions are recruited and deployed is suggested as a potential solution for improving the inter-institutional networks. The research elucidates that inter-institutional networks and transboundary institutions are two pillars that supports adaptation and also bridges the gap between adaptive capacity and adaptation manifestation that enable water institutions to cross the chasm of adaptation barriers. Thus the thesis presents an important analysis of key characteristics that enable or hinder water management institutions to adapt to climate change which have been so far under acknowledged by other studies through the analysis of the state of climate change adaptation in India. Therefore, this study provides valuable insights for developing countries, particularly, facing similar challenges of adapting water management for climate change.
Keywords: adaptive capacity; interconnected; multilevel; transboundary institutions